Revision of the sap beetle genus Pocadius Erichson, 1843 (Coleoptera: Nitidulidae: Nitidulinae) - Cline, Andrew R. (Zootaxa, 2008)
A total of 47 species are included in a revisionary treatment of Pocadius Erichson. Twenty-one species are redescribed, P. yunnanensis Grouvelle is resurrected, and 25 are described as new, including: P. antennuliferus (Brazil), P. ashei (Bolivia), P. barclayi (Sulawesi), P. bicolor (Brazil), P. carltoni (Nicaragua), P. centralis (Central America), P. cochabambus (Bolivia), P. coxus (Brazil), P. crypsis (Guyana), P. dominicus (Dominican Republic), P. endroedyi (southern Africa), P. falini (Paraguay), P. fasciatus (Borneo), P. femoralis (Vietnam), P. fusiformis (Sulawesi), P. globularis (Honduras), P. insularis (Trinidad), P. kirejtshuki (Australia), P. luisalfredoi (Mexico), P. nigerrimus (Paraguay), P. okinawaensis (Okinawa), P. pecki (Venezuela), P. peruensis (Peru), P. tepicensis (Mexico), P. wappesi (Bolivia). An adult and larval description for the genus also is provided and its phylogenetic position within Nitidulinae discussed. A key to all species is included, as well as a checklist of species and their distributions.